Biological treatment of groundwater with a high hexavalent chromium content under anaerobic and anoxic conditions. Issue 6 (4th April 2016) - Panousi, Eleni; Mamais, Daniel; Noutsopoulos, Constantinos; Antoniou, Korina; Koutoula, Kiriaki; Mastrantoni, Sevasti; Koutsogiannis, Constantinos; Gkioni, Alexandra
Abstract: BACKGROUND: Microbial reduction of Cr(VI) to the much less toxic Cr(III), although practiced for the treatment of liquid wastes has not been implemented for the treatment of groundwater due to the absence of electron donors (organic substrates) and the lack of data on inhibition of biological Cr(VI) removal. The objective of this work is to evaluate biological groundwater treatment systems that will achieve high Cr(VI) removal with addition of a low dose of organic substrate and to estimate inhibition of microbial Cr(VI) reduction under anaerobic and anoxic conditions. RESULTS: Biomass acclimatized to Cr(VI) under anaerobic conditions exhibited a higher sensitivity to Cr(VI) compared with biomass acclimatized to Cr(VI) under anoxic conditions. No significant inhibition of microbial growth was observed under anaerobic conditions for initial groundwater Cr(VI) concentrations up to 2000 µg L −1, whereas no significant inhibition was obtained under anoxic conditions at Cr(VI) concentrations as high as 10 000 µg L −1 . CONCLUSION: This study demonstrates that anoxic biological systems treating groundwater can provide complete hexavalent chromium removal at initial hexavalent chromium concentrations as high as 10 000 µg L −1 . In addition anaerobic conditions can support complete hexavalent chromium removal at initial hexavalent chromium concentrations as high as 2000 µg L −1 . © 2016 Society of Chemical Industry